Automatic braking system and smart safety features to avoid and reduce road accident - Murshed, Abrar; Anowar, Shaikh Shazib (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2021.